Pengaruh Permainan Tradisional Engklek Melalui Pendekatan Etnomatematika Terhadap Hasil Belajar Siswa Kelas V - Siti Luthvita Dewi Anis Safitri; Denni Agung Santoso; Moh. Syaffruddin Kuryanto (Universitas Veteran Bangun Nusantara, 2024)
One mathematical idea that is present in a culture is ethnomathematics. Learning and the outcomes of mathematics education will be greatly impacted by the presence of mathematicians with cultural subtleties. The purpose of this study is to ascertain how the traditional engklek game affects class V students' learning outcomes in mathematics. This study uses a pre-experimental design and is quantitative in nature. Pretest, posttest, documentation questions, and direct literature reviews of participants were the tools utilized in this study. The Normality Test, Hypothesis Test, and N-Gain Test were among the data analysis methods used in the interim. The study's findings demonstrate that the classic game of engklek has an impact and can enhance fifth-grade students' learning outcomes in mathematics.